A Cross Sectional Study on Peak Expiratory Flow Rate (PEFR) and BMI among construction site workers in Chennai District of Tamilnadu - Dr. Priya P; Dr. Sagetha (The Bioscan, 2024)
Background: The construction industry is undeniably one of the most hazardous job environments.1 Obese people are more likely to experience respiratory symptoms. Peak Expiratory Flow Rate (PEFR) is the most commonly used pulmonary function test to evaluate the respiratory health status. Objective: The objectives was to assess the association of BMI with PEFR which reflects the respiratory function of construction workers and to study possible factors associated with the respiratory function of these construction workers. Methods: An observational cross sectional study was carried out on 100 healthy construction workers from various construction sites at Thirunelveli district. Data on socio demographic profile and information regarding the smoking and comorbidities status, height, weight, BMI was estimated and Peak Expiratory Flow Rate was measured using peak flow meter. Results: The mean age of the study participants was 34.4+12.2 years, BMI was 23.14+3.7, height was 156.4+11.1 cm and weight was 57.3+13.1 kg. It was found that as the years of experience increases, PEFR is reduced. Among those participants who smoke majority of them had reduced PEFR values and majority of study participants who were overweight and obese had abnormal PEFR values. Conclusion: According to the current study, the obese population has impaired peak expiratory flow rate (PEFR). Smoking and increased number of years of experiences impacts the lung function.